Catholicism, the Church, and their cosmopolitics: a reflective aproach - Sena, Emerson (2025)
The objective of this article is to investigate, albeit briefly, the cosmopolitics that animate Catholicism and the Church. It asks what their essential characteristics and forms are. The purpose of the text was to discuss, in introductory notes, the existence of these configurations in the identity of Catholicism and the Church. As a qualitative hypothesis, it is proposed that these essential characteristics and forms of cosmopolitics are derived from the relationship between the institution and religious expression (Catholics) during its historical existence. The methodology has been qualitative. In order to answer the question, bibliographic-theoretical notes, ideal types, and certain historical traces were used.